2021
DOI: 10.3390/agronomy11112329
|View full text |Cite
|
Sign up to set email alerts
|

Physiology, Growth, and Productivity of Spring–Summer Black Gram (Vigna mungo L. Hepper) as Influenced by Heat and Moisture Stresses in Different Dates of Sowing and Nutrient Management Conditions

Abstract: Heat and soil moisture stress account for serious abiotic constraint in black gram (Vigna mungo (L.) Hepper) production during spring–summer under Gangetic plains of Eastern India. Concurrence of these two can bring about early completion of phenophases that hampers normal metabolism of legumes by disrupting their defense mechanism, leading to poor seed set. The field experiment was conducted with two different sowing dates as the main plot, soil application of cobalt (Co) as subplots and foliar sprays of pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Proline accumulation is one of the major mechanisms of drought tolerance in plants [ 113 , 114 ]. Stress tolerance through the accumulation of proline has been reported to be intensified through the foliar spray of K [ 115 , 116 ]. Potassium deficiency has also been linked to a significant reduction in the rate of photosynthetic CO 2 fixation, partitioning and use of photosynthates in moisture-deprived conditions [ 117 , 118 ].…”
Section: Nutrient Management Approaches To Alleviate the Abiotic Stre...mentioning
confidence: 99%
See 1 more Smart Citation
“…Proline accumulation is one of the major mechanisms of drought tolerance in plants [ 113 , 114 ]. Stress tolerance through the accumulation of proline has been reported to be intensified through the foliar spray of K [ 115 , 116 ]. Potassium deficiency has also been linked to a significant reduction in the rate of photosynthetic CO 2 fixation, partitioning and use of photosynthates in moisture-deprived conditions [ 117 , 118 ].…”
Section: Nutrient Management Approaches To Alleviate the Abiotic Stre...mentioning
confidence: 99%
“…Boron (B) application has a significant impact on reducing the negative effects of abiotic stress, improving yield, and nutrient uptake. Boron plays a vital role in the overall metabolism and transport system of carbohydrates as well as synthesis and functional aspects of cellular integuments [ 116 , 210 ]. Application on B mitigates the negative effects of saline environments by maintaining internal K + balance through retaining cell wall elasticity and recovery of proper levels of K + [ 211 ].…”
Section: Nutrient Management Approaches To Alleviate the Abiotic Stre...mentioning
confidence: 99%
“…Higher plant height produced more leaves which lead to higher leaf area index in delayed sowing. Banerjee et al [11] [12], who reported as increased dosage of fertilizers (37.5:75:37.5 NPK kg ha -1…”
Section: Effect Of Sowing Windows and Nutrient Levels On Leaf Area Indexmentioning
confidence: 99%
“…More than 87% of the area under pulses is presently rainfed and moisture stress is the main reason for crop failure or for low yield realization. Water deficit stress can lead to various physiological peculiarities in plants, getting in the way of their growth and production (Banerjee et al, 2021). In fact, this abiotic stress appearing at the reproductive phase of plants may pose serious threats to the maturing of leguminous crops by means of leaf area and chlorophyll content ultimately culminating into poor production (Banerjee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Water deficit stress can lead to various physiological peculiarities in plants, getting in the way of their growth and production (Banerjee et al, 2021). In fact, this abiotic stress appearing at the reproductive phase of plants may pose serious threats to the maturing of leguminous crops by means of leaf area and chlorophyll content ultimately culminating into poor production (Banerjee et al, 2021). Improved varieties of different pulse crops hold promise to increase productivity by 20-25% (Ali and Gupta, 2012).…”
Section: Introductionmentioning
confidence: 99%